A Decision-making Support System Providing Data-based Analysis of Current Competition in the Industry - Hui Kim, Ji; Jun, Seung-pyo; Sun Yoo, Hyoung (International Journal of Engineering and Technology, 2019)
Small and medium enterprises need a wide range of information regarding technologies, industries, market conditions, other companies, and products to help them identify new growth opportunities and to respond quickly to changes in the business environment. Collecting such information, however, requires the input of resources (human resources, cost, and time), and the lack of marketability resulting from the shortage of such resources is often cited as the reason small and medium often fail in their attempts to commercialize their technology. The main purpose of this study is to analyze environmental factors such as market concentration and the current level of competition to help companies make the necessary decisions when considering market entry following R&D planning and technology commercialization or after the development of a new product. Our goal is to provide more objective and reliable data by conducting data-based analyses of the current level of competition and other economic and technological factors within an industry. The industry or market data used in this study were analyzed based on the annual sales of the companies within the entire industry, and this industry or market data was classified using the Korea Standard Industry Code Korea Standard Industry Code (KSIC). The studyâ€™s outcomes were applied to develop an analysis module for KMAPS, an intelligence system for industry and market analysis. The outcome of this study is a growth opportunity index that makes it possible to see the competitive structure of an industry at a single glance, which we believe will help prevent failures in commercialization. Furthermore, an expert-based 5FORCE analysis can be performed using KMAPS, an industry and market intelligence system: this makes it possible to automatically produce analyses based on corporate finance and transaction data. The key contribution of the study is that it makes it possible to conveniently and quickly analyze 5 Forces, which had been a difficult task in environmental analysis, and that the outcomes of this study help companies in the decision-making process.Â Â